1994
DOI: 10.1111/j.1398-9995.1994.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of terbutaline inhaled by Turbuhaler® and by a chlorofluorocarbon (CFC) inhaler in children with exercise‐induced asthma

Abstract: The present study compared the bronchodilating effect of inhalation from the Turbuhaler (0.5 mg terbutaline x 2) with the effect of inhalation from the chlorofluorocarbon (CFC) inhaler (0.25 mg terbutaline x 4) in children aged 9-17 years with reproducible, exercise-induced asthma (EIA). The treatments were given on two occasions, 5 min apart (terbutaline 0.5 mg + 0.5 mg). The study was performed as a double-blind, double-dummy, and placebo-controlled trial in 12 asthmatic children. The study was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Eighty nine papers provided 84 trials (see www.ncchta.org/execsumm/summ526.htm for details) that were included in the review (with nine trials being duplicate publications of trials already included). 4 – 16 2086 Four of the included trials 74 8385 reported more than one trial in their paper or had additional independent trial arms that met our inclusion criteria and were therefore analysed as separate trials. We wrote to 78 authors of the 80 included trials for further information and received 34 replies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty nine papers provided 84 trials (see www.ncchta.org/execsumm/summ526.htm for details) that were included in the review (with nine trials being duplicate publications of trials already included). 4 – 16 2086 Four of the included trials 74 8385 reported more than one trial in their paper or had additional independent trial arms that met our inclusion criteria and were therefore analysed as separate trials. We wrote to 78 authors of the 80 included trials for further information and received 34 replies.…”
Section: Resultsmentioning
confidence: 99%
“…2022 6372 Most trials were in patients with mild to moderate asthma, as defined by a baseline forced expiratory volume in one second >50% of predicted.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, one study claimed that the Turbohaler was an effective alternative to CFC-MDI for the delivery of an identical dosage of terbutaline 43. Twelve subjects completed the crossover trial.…”
Section: Discussionmentioning
confidence: 99%
“…If a study is performed at only one dose level for each of the devices, it is not possible to verify that the response is on the slope of the dose-response curve if no difference between the two ways of administering the drug is observed. Unfortunately, many of the studies presented in the literature [8,[72][73][74][75][76][77][78] have an inadequate design and are, thus, inconclusive. A well-designed comparative study should include at least two dose levels, for at least one of the devices, and it is necessary to show a difference in the response between the two dose levels to draw conclusions.…”
Section: Airway Effectsmentioning
confidence: 99%
“…Terbutaline Turbuhaler® and pMDI were compared with respect to the bronchodilating effect after exerciseinduced bronchoconstriction [73]. A dose of 0.5 plus 0.5 mg was given to children after exercise, and it was found that the effects on reversing of the exercise-induced asthma were similar after Turbuhaler® and pMDI.…”
Section: Terbutalinementioning
confidence: 99%